Baseline Study on Extended Distribution and a Note on Threat Assessment of Crinum woodrowii from Northern Western Ghats - Mahajan, D.M.; Bhagwat, Mayur Mahendra (Indian Forester, 2025)
Crinum woodrowii Baker, a critically endangered bulbous plant in the Amaryllidaceae family, was historically limited to Kates Point, Mahabaleshwar, India. It was rediscovered in 2004 after being thought extinct. This study aimed to assess its new distribution and threats. Over the past six years, eleven additional populations have been identified in the Northern Western Ghats, expanding its known altitudinal range from 22 m to 1275 m. The species is now known to have a total of 1,666 mature individuals, with no subpopulation exceeding 250. Its Extent of Occurrence (EOO) is 26,875.811 kmÂ² and its Area of Occupancy (AOO) is 64 kmÂ², qualifying it as "Endangered" under IUCN criteria (EN B2 b (iii, iv) c(iv); C2a(i)). Key threats include habitat loss from infrastructure development, shifting cultivation, and tourism, leading to significant habitat degradation and population decline, particularly at few locations. Additionally, biotic threats such as predation and bulb exploitation further endanger the species. This research highlights the urgent need for conservation actions to protect newly discovered populations of C. woodrowii, providing crucial baseline data for future efforts.